A fully dynamical description of time-resolved resonant inelastic X-ray scattering of pyrazine - Freibert, Antonia; Mendive-Tapia, David; Vendrell, Oriol; Huse, Nils (Physical chemistry, chemical physics, 2024)
Recent advancements in ultrashort and intense X-ray sources have enabled the utilisation of resonant inelastic X-ray scattering (RIXS) as a probing technique for monitoring photoinduced dynamics in molecular systems. To account for dynamic phenomena like non-adiabatic transitions across the relevant electronic state manifold, a time-dependent framework is crucial. Here, we introduce a fully time-dependent approach for calculating transient RIXS spectra using wavepacket dynamics simulations, alongside an explicit treatment of the X-ray probe pulse that surpasses Kramers-Heisenberg-Dirac constraints. Our analysis of pyrazine at the nitrogen K-edge underscores the importance of considering nuclear motion effects in all electronic states involved in the transient RIXS process. As a result, we propose a numerically exact approach to computationally support and predict cutting-edge time-resolved RIXS experiments.
Zuerst veröffentlicht: 30. Juli 2024
Gesehen am 23.07.2025